2009
DOI: 10.1074/jbc.m109.020263
|View full text |Cite
|
Sign up to set email alerts
|

A Monomeric Chicken IgY Receptor Binds IgY with 2:1 Stoichiometry

Abstract: Fc receptors link the specificity of the adaptive immune system with the effector mechanisms of innate immune cells. In birds and reptiles, IgY is the principal serum antibody, and both mammalian IgG and IgE have evolved from an IgY-like ancestor, so studies of IgY offer insights into their origins (1). The historical contribution of chicken immunology to a wider understanding of the subject has been considerable (2), and recently several chicken IgY-Fc receptors have been identified. In this paper, the chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…The tyrosine residue at position 363 is highly conserved among amphibian, reptile, and avian species (Taylor et al, 2010). The X-ray crystallographic structure of the IgY-Fc fragment of chicken showed that PEGLY at positions 359-363 forms the ␣-helix followed by the turn and bend structure at the C-terminal, which are located in an exposed loop in close proximity to another loop of the C 4 domain (Taylor et al, 2009). Thus, it seems likely that the aromatic side chain at Y363 directly or indirectly contributes to an interaction with an unidentified IgY receptor for egg yolk transport.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The tyrosine residue at position 363 is highly conserved among amphibian, reptile, and avian species (Taylor et al, 2010). The X-ray crystallographic structure of the IgY-Fc fragment of chicken showed that PEGLY at positions 359-363 forms the ␣-helix followed by the turn and bend structure at the C-terminal, which are located in an exposed loop in close proximity to another loop of the C 4 domain (Taylor et al, 2009). Thus, it seems likely that the aromatic side chain at Y363 directly or indirectly contributes to an interaction with an unidentified IgY receptor for egg yolk transport.…”
Section: Discussionmentioning
confidence: 97%
“…This result suggests that the N408 carbohydrate chain plays a more critical role in IgY uptake into egg yolks than does the N308 carbohydrate chain. The N408 carbohydrate chain is located near the C 3/C 4 interface in the 3D structure (Taylor et al, 2009), so that deletion of the N408 carbohydrate chain may influence the conformation of IgY-Fc, and perhaps result in extremely lowered IgY-Fc uptake into egg yolks. Another finding of the present study is that the absence of either the N308 carbohydrate chain or N408 carbohydrate chain reduced blood IgY-Fc concentrations to nearly the same extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chicken receptor CHIR-AB1, encoded by a gene lying within the chicken LRC, binds to a position on its ligand IgY equivalent to that bound by FcαRI on IgA. The chicken IgY-CHIR-AB1 interaction also shares the 2:1 ligand:receptor stoichiometry (Purzel et al, 2009;Taylor et al, 2009Taylor et al, , 2010. The evolutionary implications are that a major shift occurred in the mode of Fc receptor binding during the evolution of mammalian IgG and IgE, such that there was a migration away from receptor recognition of the Fc interdomain region (exemplified by the Cα2/Cα3 interface in IgA) to a site in the N-terminal region of the Cγ2/ Cε3 domain.…”
Section: Ligand Bindingmentioning
confidence: 98%
“…Immunoglobulin Y (IgY) is the principal serum antibody in birds and reptiles, and an IgY-like molecule was the evolutionary precursor of both mammalian IgG and IgE [1]. The IgY heavy chain consists of four constant domains, and the Fc fragment mainly contains two constant domains on the C-terminal, the Cυ3 domain and the Cυ4 domain [2,3].…”
Section: Introductionmentioning
confidence: 99%